2015
DOI: 10.1590/s0100-736x2015000600002
|View full text |Cite
|
Sign up to set email alerts
|

Oestrus ovis infection of grazing sheep during summer in southern Chile

Abstract: ABSTRACT. - Oestrus ovis is a botfly whose larvae cause nasal myiasis, an environmental-dependent disease in small ruminants, generating acute and chronic injuries in the cranial cavities of sheep. Chile is a country of the southernmost worldwide distribution of this parasite, and there is few information about. Whence, the objective of this study was to approximate the epidemiological situation of O. ovis infection in Chilean sheep. From December 2009 to March 2010, a total of 87 samples were obtained by necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…(2015) and Hidalgo et al (2015). Mean larval burden in goats was similar with that reported by Papodopolus et al (2010) and lower than reported by Gebremedhin (2011).…”
Section: Resultssupporting
confidence: 85%
“…(2015) and Hidalgo et al (2015). Mean larval burden in goats was similar with that reported by Papodopolus et al (2010) and lower than reported by Gebremedhin (2011).…”
Section: Resultssupporting
confidence: 85%
“…Our findings showed 19% of the prevalence of O. ovis in the highlands of Ecuador. Previously, other studies carried out in South America showed a prevalence of oestrosis of 13.7% and 16.9% in Brazil [10,21], 60% in Chile [12], and 33.4% in Mexico [14]. All these studies were carried out in different geographical and ecologic zones with different climatic conditions to our study.…”
Section: Discussionmentioning
confidence: 65%
“…Oestrosis is present in different regions and habitats and has been reported worldwide, i.e., in the Mediterranean countries of Europe and Africa [8,9], Asia, and India [1,5]. In America, this parasite was found from California to the Patagonian regions, including Central America [10-12], as O. ovis activities appear to be accustomed to high temperatures (25-28°C), strong solar radiation (116-838 Wm −2 ), and a wide range of the relative humidity (65-85%) [13]. Besides, a high prevalence was found in tropical sub-humid sites where temperature, annual rainfall, and humidity were 26°C, 900 mm, and 60-80%, respectively [14].…”
Section: Introductionmentioning
confidence: 99%
“…Among the selected articles, 18 articles reported the prevalence of oestrosis in both sheep and goats [1, 7, 21, 23, 29–42], 40 articles in sheep [3, 19, 20, 22, 43–78] and 8 articles reported only in goats [79–86]. Based on the origin of samples, 50 studies were from abattoirs [3, 19–22, 29–41, 43, 4563, 65, 70, 73, 75, 77, 79–85], 10 from farms [1, 44, 64, 67–69, 74, 76, 78, 86], 3 from free ranging flocks [66, 71, 72] and 3 from mixed flocks [7, 23, 42]. Based on the method of diagnosis, 56 studies used necropsy [1, 19–22, 29–38, 4063, 65, 66, 7077, 79–85], 4 used ELISA [7, 23, 64, 69] and 6 used combined or other methods [3, 39, 67, 68, 78, 86].…”
Section: Resultsmentioning
confidence: 99%